THE IMPACT OF SOCIAL MEDIA MARKETING ON THE RETAIL CUSTOMERS PURCHASE DECISIONS AT PUNE (International Journal of Food and Nutritional Sciences, 2022)
The primary goal of this article is to determine the impact of social media marketing on the retail customer purchasing decisions at Pune. Utilizing the nonexperimental quantitative method of research and validated questionnaires in data analysis with Mean, Person Product-Moment Correlation Coefficient (Pearson-r) and Multiple Linear Regression Analysis as statistical tools, the outcome displayed the levels of social media marketing and customer purchasing decisions through the lens of Pune customers are high, which means that these two variables are oftentimes manifested. There is a positive strong relationship between social media marketing and customer purchasing decisions It was also found out that quality content as a domain of social media marketing best influences customer purchasing decisions.